Advancing Singapore-China economic relations - Saw, Swee-Hock, 1931-; Wong, John, 1939- (Institute of Southeast Asian Studies, 2014)
"This book presents a detailed account of the development of strong and substantive economic relations that existed between Singapore and China since the time when the two countries established diplomatic ties in October 1990. The chapters provide a comprehensive discussion of the main areas of cooperation, such as the institutional framework for pursuing economic links, the Suzhou Industrial Park, the Sino-Singapore Tianjin Eco-City, investments, trade, finance, tourism and education. The economic opportunities and challenges in these economic sectors in the two countries are examined in the context of the profound political and social changes taking place in mainland China and the globalization of the world economy. The book will be invaluable to policy-makers, academics and students specializing in Chinese studies, as well as businessmen and the general public interested in seeking a greater understanding of the complex economic relations between the two nations."--Publisher's website.